Plant conservation in Mediterranean-type ecosystems - Salmerón-Sánchez, Esteban; Mendoza-Fernández, Antonio Jesús; Lorite, Juan; Mota, Juan Francisco; Peñas, Julio (Mediterranean Botany, 2021)
The present paper is an overview of state of the art in plant conservation in Mediterranean-type Ecosystems (MTEs), highlighting current studies and neglected topics. A review of the literature dealing with this issue and a general analysis of the results was performed, delving into relevant plant conservation biology topics. The main topics considered were: 1) reproductive biology and genetic conservation, 2) threat factors and effects of global change, and 3) evaluation of conservation status and protected areas selection. This study illustrates differences in the number of documents published in northern countries of the Mediterranean Basin concerning southern and eastern countries and compared with other MTEs. It also highlights the paramount importance of public organizations as funding entities. Additionally, it points to a decrease in traditional subject categories related to plant conservation and increased multidisciplinary conservation research and novel methodologies (e.g., phylogenomics, SDM). To overcome existing biases among the different MTE regions, integrating actions at a transnational level would be necessary, with standard conservation policies and strategies. Moreover, research should be supported with more important participation and funding from private entities, with a clear focus on specific conservation proposals. In contrast, certain weaknesses were detected, some related to the limited information available about threatened plant species and the scarce use of the available data from genetic conservation research in management plans. Consequently, the authors consider that future conservation efforts should be addressed to improve the knowledge of threatened MTEs’ flora and implement a manual of good practices, which would make use of the available research information to put forward more direct proposals for management and conservation.